A novel method to evaluate the time-dependent stability of reservoir landslides: exemplified by Outang landslide in the Three Gorges Reservoir - Zou, Zongxing; Luo, Tao; Zhang, Shu; Duan, Haojie; Li, Shuwen; Wang, Jinge; Deng, Yedan; Wang, Jian (Landslides, 2023)
Under the effect of long-term periodic fluctuation of reservoir water level, reservoir landslide deforms continuously and the mechanical strength of slip zone varies accordingly, resulting in the stability variation. This study proposed a new time-dependent stability evaluation method based on a temporal and spatial strength evolution model of the slip zone, with consideration of the combined effect of water level fluctuation and continuous deformation of reservoir landslide with time. Then, the method was employed to evaluate the stability of the Outang landslide in the Three Gorges Reservoir area. The results indicate that: (1) a corresponding spatio-temporal deformation model is derived for quantifying landslides with advancing deformation mode; (2) the relationship between shear strength and shear displacement of slip zone soil with different moisture content conditions and different normal stress states can be quantitatively expressed by the proposed strength evolution model; (3) the stability of Outang landslide decreases with time but at a gradually declining rate, and tends to be maintained at a critical state ultimately. Overall, this novel method establishes a direct connection between the shear strength of critical geomaterial and landslide evolution process with field monitoring data, thus enables to provide a persuasive evaluation.